2022
DOI: 10.3389/fsurg.2021.779480
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Comparisons of Percutaneous Low-Power Laser Discectomy and Low-Temperature Plasma Radiofrequency Ablation for Cervical Radiculopathy: A Prospective, Multicenter, Cohort Study

Abstract: BackgroundMinimally invasive techniques, such as percutaneous low-power laser discectomy (PLLD) and low-temperature plasma radiofrequency ablation (coblation) can be applied to treat degenerative cervical radiculopathy. However, less evidence supports the superiority of distinct minimally-invasive therapy. Our study aimed to evaluate the clinical and radiological characteristics of the PLLD and coblation for cervical radiculopathy.MethodsThis was a prospective, multicenter, cohort study (ChiCTR-ONC-17010356). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Consistent with previous data, we found that PLD treatment achieved significant pain relief and functional improvement for cervical discogenic pain 9 – 11 , 15 . The overall successful rate reported by previous studies ranged from 75 to 82% according to the Macnab Criteria 11 , 15 , similarly, we found that the good-to-excellent ratio gradually increased from 67% (1-month follow-up) to 89% at last interview (Fig. 6 c).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous data, we found that PLD treatment achieved significant pain relief and functional improvement for cervical discogenic pain 9 – 11 , 15 . The overall successful rate reported by previous studies ranged from 75 to 82% according to the Macnab Criteria 11 , 15 , similarly, we found that the good-to-excellent ratio gradually increased from 67% (1-month follow-up) to 89% at last interview (Fig. 6 c).…”
Section: Discussionsupporting
confidence: 92%
“…However, it remains unclear the role of discography in PLD. Thus, discography is not routinely performed before surgery according to the guideline in our center 15 . Patient was required not to drink or eat on the day of procedure, and sedative drug is administrated during the surgery if needed.…”
Section: Methodsmentioning
confidence: 99%
“…The conservative therapy remains the first option for cervical spondylosis, and surgical intervention can be considered for those with moderate to severe myelopathy [ 10 ]. Recently, we have demonstrated that percutaneous laser cervical discectomy achieved enduring relief for radicular symptoms caused by the cervical disc degenerative disease [ 4 ]. In this case, the patient did not present typical radiculopathy, which indicated that the cervical nerve root may be not involved with the development of the intractable hiccups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the puncturing access can be designed to avoid the injury of vital vessels, including vertebral artery, internal jugular vein, and carotid artery. In our center, this minimally invasive surgery is usually performed under local anesthesia with slight sedative, to prevent the potential spinal cord injury during laser ablation [ 4 ]. For this patient, we chose general anesthesia to block the persistent hiccup condition, so that we can perform percutaneous puncture in the anterior region of neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation